Penerapan Bus Rapid Transit (BRT) Menuju Sidoarjo Smart City - Suning suning; Pungut pungut (UIN Sultan Syarif Kasim Riau, 2015)
Sidoarjo high population growth will affect the increase in private vehicle ownership. The impact is, traffic congestion is high and the accessibility of the city into decline. Empirical data shows the growth rate of light vehicle (LV) of 6% per year, heavy vehicles (HV) 3% per year, and motorcycles (MC) 11% per year. Sidoarjo city of a sub-district of Sidoarjo, Candi and Buduran. The three districts are SSWP II development region with the main function of settlements, governance and trade and services. As the city, center of activity with a fairly rapid development, implementable policy is needed to increase the accessibility of the city from the aspect of transportation. Transport policy to reduce the use of private vehicles is sustainable transportation. This study aims to identify and analyze the conditions of the transporttation, so that sustainable transportation to Sidoarjo city can be implemented. The method used is the method of primary and secondary survey, by using descriptive analysis of qualitative and quantitative research. The results showed Sidoarjo transportation conditions have an average value of the degree of saturation (DS) of> 1, meaning that the level of service in category F is the jammed flow, low speed, volume above capacity and long queues. The contribution of carbon emissions from transportation activities in Jl.Raya Buduran amounted to 34 960 grams of CO2 / day for motor cyckle and 20,240 grams of CO2 / day for cars. The carbon emissions in Jl.Pahlawan is 59,800 grams of CO2 / day for car and 14 720 grams of CO2 / day for motor cyckle. The carbon emissions in Jl.Raya Candi is 31 264 grams of CO2 / day for motor cyckle and 26,680 grams of CO2 / day for car. The amount of carbon emissions exceeded the quality standards allowed. Thus, sustainable transport policy that is appropriate for Sidoarjo is by implementing the bus rapid transit (BRT), so that the carbon emissions due to the number of private vehicles could be reduced and people are still carrying out their activities using public transport.Key words: Bus Rapid Transit (BRT), carbom emission, Sidoarjo city, Smart City, Transportation